Association between trust in the public healthcare system and selecting a surgeon in public hospitals in Israel: a cross-sectional population study - Adi Niv-Yagoda (BMC, 2020)
Abstract Background The Israeli public health system has seen a steady decline in public trust and confidence, which has resulted in an increased rate of individuals holding private and commercial health insurance policies that allow more choice of various services (especially choose the surgeon's). This study evaluated the attitudes and beliefs of Israeli adults regarding public trust, equitability and choice within the public health system. Methods A cross-sectional telephone survey conducted among a representative random sample of Israeli adults (> 25 years). Participants responded to a 27-item questionnaire. Multivariate regression analyses were performed to determine the contribution of various socio-demographic variables to the perceptions of trust and equitability in the health system and the ability to choose a surgeon, As well as a possible links among these parameters. Results Of 865 adults that responded to the survey, most were women (51.8%), Jewish (68.6%), and married (73.0%). Trust in the public health system, the perception of the system's equitability and the public's perception of the importance of selecting a surgeon were inter-related. The results emphasize a possible association between three meaningful factors: the trust in the public health system, the perception of the system's equitability and the public's perception regarding the importance of selecting a surgeon. Conclusions Public trust in the public health system is a fundamental condition for maintaining an efficient and equitable health system in Israel. The survey suggests that uncertainty regarding the identity of the surgeon who will perform a procedure in a public hospital may be linked to a sense of insecurity and distrust of the public in the public health system. This study did not examine the causal relationship between the various factors, but the study data suggests a possible link between lower trust in the system and a lower perception of its equitability, and a subsequent associated increase in the public's desire to select a surgeon. This study suggests to recognize public trust as a central and significant tool to strengthen public health system. One of the ways to strengthen the public's confidence in the public health system could be to provide the patient with reliable information regarding parameters such as the identity of the senior surgeon in the operating room or the surgeon's suitability for the patient's medical condition.